Delirium: Clinical Presentation and Outcomes in Older COVID-19 Patients - Rozzini, Renzo; Bianchetti, Angelo; Mazzeo, Francesca; Cesaroni, Giulia; Bianchetti, Luca; Trabucchi, Marco (Frontiers in Psychiatry, 2020)
The aim of the study is to describe the clinical characteristics and outcomes of o series of older patients consecutively admitted in non-ICU ward due to SARS-CoV-2 infection (14, males 11), developing delirium. Hyperkinetic delirium with aggression and agitation was observed in 43% of cases (6/14 patients). The overall mortality rate was 71% (10/14 patients). All the 6 patients exhibiting hypokinetic delirium and 50% of patients (4/8) with hyperkinetic delirium died. Among the 4 survivors we observed two different clinical patterns: 2 patients exhibited dementia and no ARDS (acute respiratory distress syndrome), while the remaining 2 patients exhibited ARDS and no dementia. The observed different clinical patterns of delirium (hypokinetic delirium; hyperkinetic delirium with or without dementia; hyperkinetic delirium with or without ARDS) identified patients with different prognosis: we believe these observations may have an impact on the management of older subjects with delirium due to COVID-19.